Social and non‐social sensory responsivity in toddlers at high‐risk for autism spectrum disorder. Issue 10 (19th June 2021) - Gunderson, Jaclyn; Worthley, Emma; Grzadzinski, Rebecca; Burrows, Catherine; Estes, Annette; Zwaigenbaum, Lonnie; Botteron, Kelly; Dager, Stephen; Hazlett, Heather; Schultz, Robert; Piven, Joseph; Wolff, Jason; et al.
Abstract: Empirical evidence concerning sensory responsivity in young children who later develop autism spectrum disorder (ASD) remains relatively limited. It is unclear whether specific patterns or aspects of sensory responsivity underlay the emergence of the disorder. The goals of this study were to (a) examine whether social versus non‐social context impacted the expression of sensory responsivity in infants at high risk for ASD, and (b) examine if sensory responsivity in social or non‐social contexts was associated with severity of ASD symptoms. The Sensory Experiences Questionnaire 2.1 was collected for 338 infants (131 females, 207 males) at high‐risk for ASD at 12 and/or 24 months of age. High‐risk toddlers meeting diagnostic criteria for ASD ( n  = 75) showed elevated sensory responsivity in both social and non‐social contexts at 12 months of age and differences widened over the second year of life. Individuals with ASD demonstrate higher responsivity in both contexts suggestive of generalized atypical sensory responsivity in ASD. Lay Summary: Behaviors such as avoiding or noticing sensory input (e.g., sounds, touches) are often different in individuals with autism spectrum disorder (ASD) than those without. The reason for this is widely unknown. The findings from this study show that in toddlers, sensory responsivity increased in both social and non‐social situations. Therefore, the setting of sensory input does not explain these differences.